Development of an Endovascular Model of Pelvic Hemorrhage Using Volumetric Computed Tomography Validation. (August 2021) - Abdou, Hossam; Du, Jonathan; Harfouche, Melike N.; Patel, Neerav; Edwards, Joseph; Richmond, Michael; Elansary, Noha; Morrison, Jonathan J.
Purpose: Uncontrolled pelvic hemorrhage from trauma is associated with mortality rates above 30%. The ability of an intervention to reduce blood loss from pelvic trauma is paramount to its success. The objective of this study was to determine if computed tomography volumetric analysis could be used to quantify blood loss in a porcine endovascular pelvic hemorrhage model. Materials and Methods: Yorkshire swine under general anesthesia underwent balloon dilation and rupture of the profunda femoris artery, which was confirmed by digital subtraction angiography. Computed tomography angiography and postprocessing segmentation were performed to quantify pelvic hemorrhage volume at 5 and 30 minutes after injury. Continuous hemodynamic and iliofemoral flow data were obtained. Baseline and postinjury hemoglobin, hematocrit and lactate were collected. Results: Of 6 animals enrolled, 5 survived the 30-minute post-injury period. One animal died at 15 minutes. Median volume of pelvic hemorrhage was 141±106 cm 3 at 5 minutes and 302±79 cm 3 at 30 minutes with a 114% median increase in hematoma volume over 25 minutes (p=0.040). There was a significant decrease in mean arterial pressure (107 to 71 mm Hg, p=0.030) and iliofemoral flow (561 to 122 mL/min, p=0.014) at 30 minutes postinjury, but no significant changes in hemoglobin, hematocrit, or heart rate. Conclusion: Computed tomography volumetric analysis can be used to quantify rate and volume of blood loss in a porcine endovascular pelvic hemorrhage model. Future studies can incorporate this approach when evaluating the effect of hemorrhage control interventions associated with pelvic fractures.